Library Resources and Services in Agricultural Universities in India - P. Mohanathan; G. Krishnasamy (Journal of Agricultural Extension Management, 2021)
The Agricultural Universities are identified as premier institutes of higher education and research in Agricultural Technology in India. Having a common goal, there is a need for cooperation among the libraries of the Agricultural Universities. To achieve this kind of co-operation, there is a need to design and develop a unique type of library portals containing resources and services of their libraries and providing links to other University libraries. Further, there is also a need to form an educational network specialized among the Agricultural University libraries. This paper comprehensively studies the availability of electronic information resources and the services of major Agricultural Universities in India